Submonolayer copper telluride phase on Cu(111): Ad-chain and trough formation - Kißlinger, Tilman; Schneider, M. Alexander; Hammer, Lutz (Physical Review B, 2021)
We present a so-far undetected submonolayer phase of copper telluride on Cu(111) with (5×3)rect periodicity and coverage of 0.40 ML tellurium (Te), which can be grown with perfect long-range order. It is structurally characterized by a combination of quantitative low-energy electron diffraction (LEED-IV), scanning tunneling microscopy (STM), and density functional theory (DFT). We find that Te induces the formation of two-Atom-wide zig-zag troughs within the Cu(111) top layer via replacing 4 Cu atoms per unit cell by two Te atoms. Additionally, the interspace between the troughs is decorated by Cu2Te2 ad-chains sitting at hcp sites. All Te atoms exhibit the same local sixfold coordination: They occupy threefold hollow sites of the substrate and are one-sided attached to another three Cu atoms. The presented structural model is verified by a LEED-IV analysis with Pendry R factor of R = 0.174 and quantitative agreement of structural parameters with DFT predictions. It also has by far the lowest energy of all models tested by DFT and simulated STM images agree perfectly with experiment. It turns out that the new (5×3)rect phase is the most dense surface telluride phase possible on Cu(111) before bulk-like copper telluride starts to grow.
CRIS-Team Scopus Importer:2021-11-19